2018
DOI: 10.3390/ijms19061591
|View full text |Cite
|
Sign up to set email alerts
|

Structural Biology of STAT3 and Its Implications for Anticancer Therapies Development

Abstract: Transcription factors are proteins able to bind DNA and induce the transcription of specific genes. Consequently, they play a pivotal role in multiple cellular pathways and are frequently over-expressed or dysregulated in cancer. Here, we will focus on a specific “signal transducer and activator of transcription” (STAT3) factor that is involved in several pathologies, including cancer. For long time, the mechanism by which STAT3 exerts its cellular functions has been summarized by a three steps process: (1) Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 103 publications
(109 reference statements)
3
71
0
2
Order By: Relevance
“…For example, it is still relatively easy to find articles and reviews where STAT3 is described to homodimerize only upon phosphorylation of both molecules at Y705, 27 and ourselves worked under this same assumption until very recently. For example, it is still relatively easy to find articles and reviews where STAT3 is described to homodimerize only upon phosphorylation of both molecules at Y705, 27 and ourselves worked under this same assumption until very recently.…”
Section: Relative Contribution Of Specific Residues To Stat3 Dimerimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is still relatively easy to find articles and reviews where STAT3 is described to homodimerize only upon phosphorylation of both molecules at Y705, 27 and ourselves worked under this same assumption until very recently. For example, it is still relatively easy to find articles and reviews where STAT3 is described to homodimerize only upon phosphorylation of both molecules at Y705, 27 and ourselves worked under this same assumption until very recently.…”
Section: Relative Contribution Of Specific Residues To Stat3 Dimerimentioning
confidence: 99%
“…Like us, and to the best of our knowledge, the existing scientific literature on STAT3 implicitly assumes that STAT3 homodimers are formed by two identical molecules in all aspects, including PTMs. For example, it is still relatively easy to find articles and reviews where STAT3 is described to homodimerize only upon phosphorylation of both molecules at Y705, 27 and ourselves worked under this same assumption until very recently. 28 Here, we made use of the unique properties of our BiFC system to determine the relative contribution of each residue to the dimerization and intracellular distribution of unstimulated STAT3 dimers, in an experimental paradigm similar to the one we used previously for mutant huntingtin.…”
Section: Relative Contribution Of Specific Residues To Stat3 Dimerimentioning
confidence: 99%
“…Phosphorylation at Tyr705 in turn drives the dimerization of STAT3 through interaction with its SH2 domain 21 . We therefore transiently co-transfected green fluorescent protein (GFP)-tagged STAT3 and FLAGtagged STAT3 plasmids into HepG2 cells, and determined the interactions of GFP-STAT3 and FLAG-STAT3 by an immunoprecipitation (IP) assay.…”
Section: α-Mgt Suppresses the Dimerization And Nuclear Translocationmentioning
confidence: 99%
“…4a, α-MGT at dose of 20 μM markedly decreased IL-6induced interactions of GFP-STAT3 and FLAG-STAT3 monomers. Dimerizated STAT3 is then translocated to the nucleus, where it binds the specific DNA-response elements in the promoters of target genes to mediate transcription 21 . The results of immunofluorescence assay indicated that α-MGT effectively blocked IL-6-induced nuclear translocation of STAT3 in HepG2 cells (Fig.…”
Section: α-Mgt Suppresses the Dimerization And Nuclear Translocationmentioning
confidence: 99%
“…N-terminal domain is pivotal for the interaction of dimers of STAT-3 for the formation of tetramer, interaction with other regulators and the attachment of STAT-3 dimers to the sites of DNA, and protein interaction (Figure 3) (Sgrignani et al, 2018). The N-terminal domain has a leading role in dimer formation, so it is a captivating approach to inhibit the function of STAT-3.…”
Section: Targeting Stat-3 N-terminal Domainmentioning
confidence: 99%